2016
DOI: 10.1002/2015jb012441
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter? Statistical limits of paleomagnetic field reconstruction from small rock specimens

Abstract: As samples of ever decreasing sizes are being studied paleomagnetically, care has to be taken that the underlying assumptions of statistical thermodynamics (Maxwell‐Boltzmann statistics) are being met. Here we determine how many grains and how large a magnetic moment a sample needs to have to be able to accurately record an ambient field. It is found that for samples with a thermoremanent magnetic moment larger than 10−11Am2 the assumption of a sufficiently large number of grains is usually given. Standard 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 18 publications
1
65
1
Order By: Relevance
“…A recent analytical approach by Berndt et al . [] of magnetite grain assemblages found that paleointensity errors exceeded 20% and paleodirectional errors exceeded 20° for net moments of ∼10 −15 −10 −14 Am 2 . In summary, three very different independent analyses by this study, Kirschvink [] and Berndt et al .…”
Section: The Need For Ultra‐high Sensitivity Moment Magnetometrymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent analytical approach by Berndt et al . [] of magnetite grain assemblages found that paleointensity errors exceeded 20% and paleodirectional errors exceeded 20° for net moments of ∼10 −15 −10 −14 Am 2 . In summary, three very different independent analyses by this study, Kirschvink [] and Berndt et al .…”
Section: The Need For Ultra‐high Sensitivity Moment Magnetometrymentioning
confidence: 99%
“…In summary, three very different independent analyses by this study, Kirschvink [] and Berndt et al . [] have found that natural samples should preserve paleomagnetically useful information down to natural remanent moments of 10 −15 −10 −14 Am 2 , 100–1000 times below that measurable with standard superconducting rock magnetometers.…”
Section: The Need For Ultra‐high Sensitivity Moment Magnetometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors estimated that when CZ islands cooled through 320°C, their diameter was ~8 nm, implying that an impractically large number of ~10 9 islands should be sampled in each XPEEM dataset to obtain statistically meaningful paleodirections and intensities (10 3 -10 4 islands are typically analyzed during a XPEEM experiment). This led Berndt et al (2016) to question the reliability of published paleomagnetic XPEEM data. However, they obtained this estimate assuming CZ islands formed through nucleation and growth, a process different from spinodal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Further, if we achieve 1 × 10 −16 Am 2 corresponding to an ~59-nm cube of magnetite, it is enough for most paleomagnetic studies because the SP/SD boundary of magnetite is around 15-50 nm (e.g., Newell and Merrill On the other hand, we may need to think about the stability of magnetic moment carried by a sample with small magnetic moment (Berndt et al 2016). Kirschvink et al (2015) reported the best sensitivity for a 2G SRM is ~10 −13 Am 2 using ultraclean quartz glass sample holder.…”
Section: −15mentioning
confidence: 99%